Chlorophyllin Modulates Gut Microbiota and Inhibits Intestinal Inflammation to Ameliorate Hepatic Fibrosis in Mice - Zheng, Han; You, Yang; Hua, Meiyun; Wu, Pengfei; Liu, Yu; Chen, Zishuo; Zhang, Li; Wei, Haoche; Li, Yan; Luo, Mei; Zeng, Yilan; Liu, Yong; et al. (Frontiers in Physiology, 2018)
Liver fibrosis is an abnormal wound healing response and a common consequence of chronic liver diseases from infection or alcohol/xenobiotic exposure. At the cellular level, liver fibrosis is mediated by trans-differentiation of hepatic stellate cells (HSCs), which is driven by persistent hepatic and systemic inflammation. However, impaired enterohepatic circulation and gut dysbiosis may indirectly contribute to the liver fibrogenesis. The composition of the gut microbiota depends on diet composition and host factors. In this study, we examined chlorophyllin, derived from green pigment chlorophyll, on gut microbiota, the intestinal mucosal barrier, and liver fibrosis. BALB/c mice received carbon tetrachloride through intraperitoneal injection to induce liver fibrosis and chlorophyllin was administrated in drinking water. The effects of chlorophyllin on liver fibrosis were evaluated for (1) survival rate, (2) hepatic morphologic analysis, (3) inflammatory factors in both the small intestine and liver, and (4) gut microbiota. Our results indicate that oral administration of chlorophyllin could attenuate intestinal and hepatic inflammation and ameliorate liver fibrosis. Importantly, oral administration of chlorophyllin promptly rebalanced the gut microbiota, exhibiting down-regulation of the phylum Firmicutes and up-regulation of the phylum Bacteroidetes. In vitro experiments on intestinal epithelial cells showed that chlorophyllin exposure could inhibit NF-κB pathway via IKK-phosphorylation suppression. In conclusion, this study demonstrates potential application of chlorophyllin to regulate the intestinal microbiota and ameliorate hepatic fibrosis.